The translingual digital practices of Saudi females on WhatsApp. (October 2018) - Albawardi, Areej
Abstract: This study examines the way young Saudi women use language and other communicative resources in their digitally mediated interactions. It is motivated by the debate in Saudi Arabia on the impact of digital media on the way people use language, especially Arabic, how they manage their social relationships, and how they enact their cultural identities. The study was conducted at a women's university in Saudi Arabia. This paper presents a descriptive analysis of participants' WhatsApp interactions, followed by an in-depth analysis of some examples, and highlights two important aspects: (1), an understudied linguistic variety used in Arabic digitally mediated communication, and (2), this paper proposes a more concrete approach to the analysis of "translanguaging, " which involves the utilization of tools from mediated discourse analysis (Jones and Norris, 2005).